2014
DOI: 10.1371/journal.pone.0096996
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Efficacy of Surgical Renal Denervation and Pharmacologic Therapies in Post-Myocardial Infarction Heart Failure

Abstract: ObjectiveAlthough renal denervation (RD) has been shown to be effective in treating post- myocardial Infarction (MI) heart failure (HF) in animal models and clinical trials, its utility as a standalone treatment without traditional drug treatment for post-MI HF still needs to be investigated.MethodsRats were randomly assigned into seven experimental groups: N group (control group with no MI and no RD, n = 10), MI group (MI, n = 20), RD group (renal denervation, n = 10), RD-3d+MI group (RD performed three days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 13 publications
1
27
0
Order By: Relevance
“…In addition, the plasma levels of BNP, which is mainly released from the ventricles and is associated with a higher mortality in heart failure [17], were significantly decreased in MI rats with RDN compared with the MI group. These observations were similar to the findings of Hu et al [18,19].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the plasma levels of BNP, which is mainly released from the ventricles and is associated with a higher mortality in heart failure [17], were significantly decreased in MI rats with RDN compared with the MI group. These observations were similar to the findings of Hu et al [18,19].…”
Section: Discussionsupporting
confidence: 93%
“…Recent animal studies in which heart failure was induced by coronary ligation in rats (47) or rapid ventricular pacing in dogs and rabbits (126,136) showed that renal denervation performed prior to the induction of heart failure improved cardiac function. Further, a pilot study in chronic heart failure patients showed improved exercise capacity following bilateral renal denervation (21).…”
Section: Pathophysiologymentioning
confidence: 99%
“…Recent clinical trials have demonstrated that renal denervation (RDN) is effective in drug-resistant hypertension to reduce the neurohumoral drive and blood pressure (13,19,39). There have been a couple of studies that have examined the effect of RDN before, or just after, myocardial infarct on cardiac function and Na ϩ excretion (14,15). Drug-resistant hypertensive patients with left ventricular hypertrophy and diastolic dysfunction show that RDN significantly reduces cardiac mass and improves diastolic function (2).…”
mentioning
confidence: 99%